KOMUNIKASI PERSUASIF SEBAGAI UPAYA MEMPERKUAT PENDIDIKAN MULTIKULTURAL - Hasanah, Uswatun; Musa, Musa; Azpa, Pani; Gustin, Gustin (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Education in the current era of globalization faces the challenge of technological disruption, necessitating serious efforts to filter communication bias, especially in the field of education. Another challenge is the abundance of negative content on social media, which poses a challenge for multicultural education among students. The low level of literacy and psychomotor competence, particularly among educators, is a hindrance to integrating multicultural education values. Additionally, the limited number of religious education teachers in schools further exacerbates this challenge, making the inculcation of multicultural education a serious issue. The technical ability of teachers, especially those who struggle to operate technology, is a practical problem that needs immediate resolution. The methodology used in this article is qualitative descriptive, drawing from various literature sources to support the study. Based on the discussion, it is concluded that persuasive communication in multicultural education can change the attitudes, behaviors, and beliefs of individuals or groups regarding certain issues, particularly in multicultural education. Persuasive communication in multicultural education has unique characteristics and provides positive effects on the audience because it has the ability to change their attitudes, opinions, and behaviors without coercion, allowing them to subconsciously follow the communicator's intentions. This communication technique, therefore, plays an essential role in multicultural education.